Would you teach in Thailand? The relationship between perceived social support, motivational cultural intelligence, cognitive cultural intelligence, and expatriates’ willingness among mandarin teachers expatriated from Mainland China - Chou, I-Wen (Edelweiss Applied Science and Technology, 2025)
Drawing on Conservation of Resources theory and the Job Demands-Resources model, this study investigates the influence of perceived social support (PSS) on expatriation willingness (EW) among 394 Chinese university Mandarin teachers, and examines the moderating effects of motivational (MCQ) and cognitive cultural intelligence (CCQ). Hypotheses are tested with SPSS 25 and Mplus. Results indicate that PSS from coworkers (β = 0.102, p = .002) and leaders (β = 0.205, p = .001) significantly positively predict EW. However, neither MCQ (β = -0.047, p = 0.595) nor CCQ (β = 0.031, p = 0.635) moderates the overall PSS–EW relationship. A notable exception is the significant negative moderating effect of CCQ (β = -0.109, p = .001) on the link between PSSC and EW. These findings highlight the complex interplay between social and cultural resources in shaping cross-cultural teaching intentions, offering practical implications for support design and talent recruitment in international educational contexts.